- Kearifan Lokal Desa Wisata Karangrejo dan Karanganyar untuk Memperkuat Ketahanan Ekonomi Desa Pasca Pandemi Covid-19 - Ahmad Zubaidi; Septiana Dwiputri Maharani; Abdul Rokhmat Sairah (Jurnal Filsafat Indonesia, 2022)
This study aims to explore the tourism potential of villages that have adopted local wisdom ofuniversal value to build and increase economic resilience in Karangrejo Village and KaranganyarVillage, Borobudur District, Magelang Regency. This research model is descriptive by taking aqualitative type of research. This research is divided into two subjects, namely the group ofparticipants who are intensively involved and the peserta who are involved incidentally. The datacollection usedis a non-test method by making observations, and direct interviews with researchsubjects and documentation data. The data that has been obtained is then analyzed with descriptive analysis techniques using Nvivo software by combining existing theories with fieldconditions. This research resulted in a description shown that the development of the potentialof wisata villages in Karangrejo and Karanganyar, Borobudur District, Magelang Regency hasadoptedlocal wisdom that contains philosophical and universal values. Local wisdom is the basisfor the development of the two tourist villages, especially for the economic recovery of thecommunity after the Covid-19 pandemic. The values of "gotong royong" or collaboration between elements of society, honesty, love of cultural arts and craft skills inherited from ancestors are able to increase the economic resilience of rural communities.